Prioritizing Susceptible Genes for Thyroid Cancer Based on Gene Interaction Network - Zhong, Lin-kun; Xie, Chang-lian; Jiang, Shan; Deng, Xing-yan; Gan, Xiao-xiong; Feng, Jian-hua; Cai, Wen-song; Liu, Chi-zhuai; Shen, Fei; Miao, Jian-hang; Xu, Bo (Frontiers in Cell and Developmental Biology, 2021)
Thyroid cancer ranks second in the incidence rate of endocrine malignant cancer. Thyroid cancer is usually asymptomatic at the initial stage, which makes patients easily miss the early treatment time. Combining genetic testing with imaging can greatly improve the diagnostic efficiency of thyroid cancer. Researchers have discovered many genes related to thyroid cancer. However, the effects of these genes on thyroid cancer are different. We hypothesize that there is a stronger interaction between the core genes that cause thyroid cancer. Based on this hypothesis, we constructed an interaction network of thyroid cancer-related genes. We traversed the network through random walks, and sorted thyroid cancer-related genes through ADNN which is fusion of Adaboost and deep neural network (DNN). In addition, we discovered more thyroid cancer-related genes by ADNN. In order to verify the accuracy of ADNN, we conducted a 5-fold cross-validation. ADNN achieved AUC of 0.85 and AUPR of 0.81, which are more accurate than other methods.